a)
"z_x=3x^3y^2+f(x)"
The general solution of the partial differential equation.
"z={3\\over 4}x^4y^2+F(x)+G(y)"b)
"z(x,0)=6x^2=>F(x)+G(0)=6x^2=>""=>F(x)=6x^2, G(0)=0"
"z(1,y)=6\\cos{y}=>{3\\over 4}y^2+6+G(y)=6\\cos{y}=>"
"=>G(y)=-{3 \\over 4}y^2+6\\cos{y}-6"
"z^*={3\\over 4}x^4y^2+6x^2-{3 \\over 4}y^2+6\\cos{y}-6"
Comments
In part b), the solution states F(x)+G(0)=6x^2. The G(0) is equal to the specific number. If F(x)=6x^2, then G(0)=0. If G(0)=a, where a is not equal to zero, then F(x)=6x^2-a. Nevertheless, this choice does not change the final expression of the particular solution.
Is G(0) equal to 0 because there is no y term on the other side of the equation? ( 2nd line of part b)
The position of 6 was not specified in the comment.
Should the 6 be positive?
Leave a comment